2022
DOI: 10.1111/oik.09617
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term spatially‐replicated data show no physical cost to a benefactor species in a facilitative plant–plant interaction

Abstract: Facilitation is an interaction where one species (the benefactor) positively impacts another (the beneficiary). However, the reciprocal effects of beneficiaries on their benefactors are typically only documented using short-term datasets. We use Azorella selago, a cushion plant species and benefactor, and a co-occurring grass species, Agrostis magellanica, on sub-Antarctic Marion Island, comparing cushion plants and the grasses growing on them over a 13-year period using a correlative approach. We additionally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(182 reference statements)
0
3
0
Order By: Relevance
“…We had hundreds of selected cushion individuals (plots) in this study ( Table 1 ) which is quite hard to do investigation on species composition, abundance and/or richness for each individual. Considering that vegetation cover could be positively correlated with plant diversity (e.g., Wiesmair et al., 2017 ), for the purpose of this study, we took the total beneficiary cover ratio (i.e., beneficiary covering area/total cushion individual surface area × %) on the cushion surface as the predictor of the facilitation intensity of cushion plants (also see Raath-Krüger et al., 2023 ). For this, we took the same protocol of assessing flower cover ratio ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We had hundreds of selected cushion individuals (plots) in this study ( Table 1 ) which is quite hard to do investigation on species composition, abundance and/or richness for each individual. Considering that vegetation cover could be positively correlated with plant diversity (e.g., Wiesmair et al., 2017 ), for the purpose of this study, we took the total beneficiary cover ratio (i.e., beneficiary covering area/total cushion individual surface area × %) on the cushion surface as the predictor of the facilitation intensity of cushion plants (also see Raath-Krüger et al., 2023 ). For this, we took the same protocol of assessing flower cover ratio ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For A. selago specifically, a very slow vertical growth rate of 0.43 ± 0.01 cm/year (mean ± SE) has been reported for Marion Island (see le Roux & McGeoch, 2004). In contrast, using a long‐term data set of repeated measures to examine the outcome of plant–plant interactions, Raath‐Krüger et al (2022) reported that A. selago diameter increases more quickly (i.e., by 1.98 ± 0.07 cm/year). Due to the longevity of A. selago plants (le Roux & McGeoch, 2004), the ability of the species to create a microhabitat unique from that of the surrounding matrix (e.g., Nyakatya & McGeoch, 2008; le Roux & McGeoch, 2008b; Haussmann et al, 2009), and with minimal variation in abiotic conditions at the scale of 1 m on the landform, a paired sampling approach was considered well suited for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Cushion plants are often long‐lived and some species can survive for several hundreds of years (Morris & Doak, 1998). However, given that it is impossible to study these plants over a lifetime, examining the performance of these plants from long‐term data sets may provide deeper insights into the long‐term balance of plant interactions (see, e.g., Raath‐Krüger et al, 2022). For A. selago specifically, a very slow vertical growth rate of 0.43 ± 0.01 cm/year (mean ± SE) has been reported for Marion Island (see le Roux & McGeoch, 2004).…”
Section: Methodsmentioning
confidence: 99%